Flame retardant having anti-dripping function, method for preparing the same, and thermoplastic resin composition
Patent Information
- Application Number
- CN202611477937.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-27
AI Technical Summary
目前,市场上主流的抗滴落剂为含氟聚合物(如聚四氟乙烯(PTFE)在加工后能通过纤维化作用提高熔体强度,抑制熔滴),但此类含氟抗滴落剂含有卤素,在燃烧时会释放有毒有害气体
相对于现有技术,本申请提供的具有抗滴落功能的阻燃剂中不含有卤素,在高温燃烧时不会释放有毒有害气体,且符合环保要求。
Smart Images

Figure CN122978167A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of organic polymer compounds, specifically relating to flame retardants with anti-dripping function, their preparation methods, and thermoplastic resin compositions. Background Technology
[0002] Thermoplastic resins (such as polyamides, polyesters, and polyolefins) are widely used due to their excellent overall properties. However, most of these materials are flammable and produce high-temperature molten droplets when burning. These droplets can easily ignite surrounding combustibles as mobile ignition sources, causing secondary fires or even chain reactions, posing a significant safety hazard.
[0003] In glass fiber reinforced thermoplastic resin systems, the physical skeleton support of glass fiber, the restriction of molecular chain movement, the assistance in char formation and the barrier can improve anti-dripping performance. Therefore, the focus is usually on solving the "candle wick effect" of glass fiber, and there is no need to solve the anti-dripping problem in the flame retardant process. However, the technical difficulty of inhibiting melt dripping in pure thermoplastic resin is high, which is a long-standing industry pain point in the field of flame retardant modification of thermoplastic resin.
[0004] To address this deficiency, existing technologies typically employ a combination of anti-dripping agents and flame retardants to enhance the flame-retardant and anti-dripping properties of thermoplastic resins. Currently, the mainstream anti-dripping agents on the market are fluoropolymers (such as polytetrafluoroethylene (PTFE), which can improve melt strength and suppress dripping through fiberization after processing). However, these fluorinated anti-dripping agents contain halogens, which release toxic and harmful gases during combustion.
[0005] In addition, some flame retardants that inhibit dripping are used directly. However, these flame retardants often have high viscosity or undergo partial cross-linking reactions when the resin processing temperature is reached (e.g., 260~280℃, and the actual shear temperature can reach over 300℃), resulting in a sudden increase in viscosity and thus affecting the resin processing and molding performance.
[0006] Therefore, there is a need to develop a new type of halogen-free flame retardant with anti-dripping properties that does not affect resin processing. Summary of the Invention
[0007] To address the problems described in the background section, the present invention aims to provide a novel halogen-free flame retardant with anti-dripping function that does not affect resin processing, its preparation method, and a thermoplastic resin composition thereof. Specifically, this is achieved through the following technical solutions: Flame retardants with anti-dripping properties, including flame retardants of Formula I: Formula I, R1 is selected from phenyl or phenoxy. R2 is selected from hydrogen and cyano. R3 is selected from one of methylene, ethylene, phenyl, and acetylated groups. The R4 is either R1 or N-R2(R3-CN), and the N-R2(R3-CN) group is connected to the P in Formula I through N.
[0008] Optionally, the flame retardant is selected from one or more of the flame retardants with structures (1) to (7). .
[0009] Optionally, the flame retardant is prepared by a nucleophilic substitution reaction of a phosphoryl chloride compound and an aminocyanide, wherein the phosphoryl chloride compound includes one or more of diphenyl chlorophosphate, phenylphosphonic dichloride, and diphenylphosphine chloride.
[0010] Optionally, the aminocyanide includes one or more of aminoacetonitrile, 3-aminopropionitrile, iminodiacetonitrile, m-aminobenzonitrile, 2-aminobenzonitrile, cyanoacetamide, and p-aminobenzonitrile.
[0011] This application also provides a method for preparing the flame retardant described in any of the above technical solutions, comprising the following steps: a phosphoryl chloride compound undergoes a nucleophilic substitution reaction with an aminocyanide, and one or more post-treatment methods such as separation, purification, and drying are performed as needed to prepare the flame retardant of Formula I.
[0012] Optionally, the molar ratio of the phosphoryl chloride compound to the aminocyanide is 1:(1~2.5).
[0013] Optionally, the nucleophilic substitution reaction is carried out at a temperature of 70-90 °C for 16-20 h.
[0014] This application also provides a thermoplastic resin composition comprising the flame retardant with anti-dripping function described in the above technical solutions.
[0015] Optionally, the thermoplastic resin composition uses one or more of polyamide, polyester, and polyolefin resins as the resin matrix, and the flame retardant of Formula I is a non-reactive flame retardant.
[0016] Optionally, the thermoplastic resin composition may further include one or more of the following: reinforcing filler, antioxidant, lubricant, toughening agent, antistatic agent, laser marking agent, and color powder.
[0017] Optional, by parts by weight, it includes the following components: 62-92 parts of thermoplastic resin; Flame retardant 8-25 parts; 0-20 parts of mineral powder; The sum of the above components is 100 parts by mass.
[0018] Optional, by parts by weight, it includes the following components: 86-90 parts of thermoplastic resin; 10-14 parts flame retardant; The sum of the above components is 100 parts by weight, and the composition achieves a flame retardant rating of V-0 at a thickness of 3.2 mm.
[0019] Compared with the prior art, this application has the following beneficial effects: Compared to existing technologies, the flame retardant with anti-dripping function provided in this application does not contain halogens, does not release toxic or harmful gases when burning at high temperatures, and meets environmental protection requirements.
[0020] Compared with the prior art, the flame retardant with anti-dripping function provided in this application can significantly suppress dripping or even completely eliminate it when added to thermoplastic resin. This may be because the flame retardant described in this application undergoes a triazine reaction under high combustion conditions, forming a network structure that restricts chain segment movement, increasing melt viscosity and preventing dripping. This is different from the conventional principle of preventing dripping through char formation and physical interactions (such as the formation of hydrogen bonds, π-π stacking, etc.).
[0021] Compared with the prior art, the flame retardant with anti-dripping function provided in this application has good flame retardant effect when added to thermoplastic resin. When added to polyamide resin, the flammability rating can reach V-0 at a thickness of 3.2mm. The possible flame retardant mechanism is as follows: The flame retardant described in this application pyrolyzes under high-temperature combustion conditions to produce phosphorus-containing volatile fragments and releases a large amount of ammonia gas, which dilutes oxygen and combustible volatiles. The PO· and PO2· free radicals formed by the subsequent further cracking of the phosphorus-containing volatile fragments can capture active H· and OH· free radicals in the flame zone.
[0022] This application adds a flame retardant of formula 1 to a thermoplastic composition. The melt viscosity of the composition only begins to increase significantly above approximately 340°C, without affecting the melt processing of thermoplastic resins with processing temperatures below 340°C, especially extrusion and injection molding. Some cyano compounds with char-forming properties, although capable of improving flame retardancy and other properties through triazine crosslinking reactions, lead to a significant increase in melt viscosity during the melt processing of thermoplastic resin compositions. For example, a substantial increase occurs between 230 and 300°C, making direct application in the processing of thermoplastic resins almost impossible. For instance, the conventional melt processing temperature for PP is typically controlled between 190 and 260°C, while PET, PBT, PA6, and PA66 typically require extrusion and injection molding temperatures above 230°C. High-viscosity melts are difficult to melt process and prone to causing problems during injection molding. This prevents the parts from being fully filled, making injection molding of thin-walled parts almost unusable. This may be because the phosphoxy group is a strong electron-withdrawing group. This group can reduce the electron cloud density around the benzene ring and cyano group through the conjugation / induction effect with the amino and benzene rings. As a result, the nucleophilic reactivity of the cyano group is reduced, which increases the activation energy of the crosslinking reaction. In addition, the amino group in the flame retardant molecule forms intermolecular and intramolecular hydrogen bonds with the phosphoxy group, which restricts molecular motion and makes it difficult for the cyano groups to approach and collide effectively, further delaying the crosslinking reaction. At the same time, the large size of the diphenylphosphono group forms a significant spatial shielding effect on the cyano group, hindering the crosslinking of the cyano group. Attached Figure Description
[0023] Figure 1 For flame retardant 1 1 H NMR spectrum; Figure 2 For flame retardant 1 31 P NMR spectrum; Figure 3 The image shows the FT-IR spectrum of flame retardant 1. Figure 4 The image shows the LC-MS spectrum of flame retardant 1. Figure 5 The LC-MS spectrum of flame retardant 2 is shown below. Figure 6 The image shows the LC-MS spectrum of flame retardant 3. Figure 7 The image shows the LC-MS spectrum of flame retardant 4. Figure 8 The image shows the LC-MS spectrum of flame retardant 5. Figure 9 The image shows the LC-MS spectrum of flame retardant 6. Figure 10 The TG-DTG diagram of the thermoplastic resin composition in Example 7 is shown below. Figure 11This is a comparison graph showing the viscosity changes of PA66 resin in Comparative Example 5 and the thermoplastic resin composition in Example 7. Detailed Implementation
[0024] The specific implementation methods of this application are described in detail below through examples. However, the examples of this application are not intended to limit the technical solutions of this application. Any non-substantial changes, such as replacing common technical solutions in the field, using the technical solutions described in the examples of this application are within the protection scope of this application.
[0025] The raw materials used in the embodiments and comparative examples of this invention are as follows, but are not limited to these materials. Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application can all be obtained commercially: Diphenylphosphine chloride, CAS: 1499-21-4; Benzyl dichloro, CAS: 824-72-6; Aminoacetonitrile, CAS: 540-61-4; Iminodiacetonitrile, CAS: 628-87-5; p-Aminobenzonitrile, CAS: 873-74-5; 2-Cyanoacetamide, CAS: 107-91-5; Triethylamine, CAS: 121-44-8; Acetonitrile, CAS: 75-05-8; Ethanol, CAS: 64-17-5; Melamine, 108-78-1; PA6, Tianjin Haijing, 2702BR; PET, Jiangyin Huitai New Materials FG600; PP, Zhejiang Hongji PPH225; PA66, Yangnong Ruitai YN2700; PBT, Zhejiang Changhong CH810; Antioxidant 1098, commercially available; Antioxidant 168, commercially available; 1250 mesh talc powder S-8, commercially available; The test methods and standards used in each comparative example and embodiment are as follows: Nuclear magnetic resonance (NMR) spectrometer, 400 MHz, ASTM E2977-15(2023); Fourier transform infrared spectroscopy (FT-IR) was performed using the potassium bromide pellet method, according to ASTM E1252-98 (2021). Differential scanning calorimetry (DSC): ISO 11357-3-2018; Thermogravimetric analysis (TG): ISO 11358-1:2014; Liquid chromatography-mass spectrometry (LC-MS): ISO 17025-2017; The structure of the flame retardant was characterized by nuclear magnetic resonance (NMR), Fourier transform infrared spectroscopy (FT-IR), and liquid chromatography-mass spectrometry (LC-MS), and its thermal properties were characterized by differential scanning calorimetry (DSC) and thermogravimetric analysis (TG).
[0026] Flame retardancy rating: Injection-molded 3.2mm thick standard test strips, tested according to ASTM-D3801-26, which is equivalent to the ANSI / UL 94 20 mm (50W) vertical burning test (V-0, V-1, V-2).
[0027] Droplet count: Record the average number of molten droplets that fall during the vertical burning process of UL94 (rounded up). For example, if the average is 1.2 drops, it is recorded as 2 drops.
[0028] Injection molding methods are common knowledge to those skilled in the art and can be adjusted according to the type of resin matrix and formulation, so they will not be elaborated further.
[0029] The limiting oxygen index was tested according to ASTM D2863-17 standard, and the sample size was 100mm × 6.5mm × 3.2mm.
[0030] The preparation method of the flame retardant with anti-dripping function in the embodiments of this application is shown below. It should be noted that the mechanism of nucleophilic substitution reaction is common knowledge. Those skilled in the art can obtain the flame retardant of Formula I by controlling the raw materials and reaction conditions according to the embodiments and comparative examples.
[0031] A method for preparing a flame retardant with anti-dripping properties includes the following steps: A flame retardant with anti-dripping function was prepared by reacting phosphoryl chloride compounds with aminocyanide through a nucleophilic substitution reaction, followed by separation, purification, and drying.
[0032] It should be noted that the separation, purification, and drying (if necessary) in the above methods can be performed by those skilled in the art as needed. For example, purification can be achieved by washing with ethanol and / or water multiple times. In all the embodiments and comparative examples of this application, purification treatment was performed by washing with ethanol and deionized water three times. Separation can be achieved by vacuum filtration or rotary evaporation. Example 1
[0033] 0.25 mol of p-aminobenzonitrile (ABN) and 0.25 mol of triethylamine were dissolved in 200 ml of acetonitrile and placed in a reaction vessel. 0.25 mol of diphenylphosphine chloride (DPC) was dissolved in 60 ml of acetonitrile and added dropwise to the reaction vessel. Nitrogen gas was continuously purged to replace air during the process. After the addition was completed, the mixture was stirred continuously at 20 °C for 1.5 h. Then the temperature was raised to 85 °C and the nucleophilic substitution reaction was carried out for 18 h. The product was then separated, purified, and dried to obtain flame retardant 1 with a yield of approximately 84%.
[0034] The solvent acetonitrile used in this embodiment can be replaced with acetone, dichloromethane, trichloromethane, N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), tetrahydrofuran, etc., in other embodiments according to actual needs.
[0035] In this embodiment, the amino group on p-aminobenzonitrile undergoes a nucleophilic substitution reaction with the hypophosphite chloride group on diphenylphosphite chloride. The specific reaction equation is as follows:
[0036] Thermal performance test results: The melting temperature of this flame retardant is 226.2 ℃, and the initial decomposition temperature is 318.3 ℃.
[0037] Figure 1 For flame retardant 1 1 The 1H NMR spectrum showed that the peaks at 7.19–7.83 ppm corresponded to the 14 hydrogens on the benzene ring, and the peaks at 8.89–8.92 ppm corresponded to the protons on the p-NH group, indicating that the nucleophilic substitution reaction had successfully formed the phosphoramide structure.
[0038] Figure 2 For flame retardant 1 31 The NMR spectrum showed a single resonance peak at 17.39 ppm, indicating that all phosphorus atoms in flame retardant 2 are in the same environment. This result is consistent with the formation of PN bonds, further proving that the nucleophilic substitution reaction has successfully formed the phosphoramide structure.
[0039] Figure 3 The images show the FT-IR spectra of p-aminobenzonitrile and flame retardant 1. The results show that both exhibit similar characteristics at 2223 cm⁻¹. -1 The characteristic peak of the cyano group at 3479 and 3376 cm⁻¹ remains unchanged, indicating that the cyano functional group is retained during the synthesis of flame retardant 1. The -NH₂ group in ABN remains unchanged at 3479 and 3376 cm⁻¹. -1 The peak at 3409 cm⁻¹ disappears, while in flame retardant 4, the peak at 3409 cm⁻¹ disappears. -1 A new peak appears at 927 cm⁻¹, corresponding to the NH group. -1 The peak at 1494 cm⁻¹ corresponds to the PN group. -1The peak corresponds to the P-Ph group, 1249 cm⁻¹ -1 The peak corresponds to the P=O group.
[0040] Figure 4 The image shows the LC-MS spectrum of flame retardant 1. The results indicate that the molecular ion peak is located at m / z 319.2 [M+H]. + This is consistent with the expected molecular weight of the target flame retardant, which is 318.3 g / mol.
[0041] In summary, the synthesis of flame retardant 1 can be proven. Example 2
[0042] 0.25 mol aminoacetonitrile and 0.25 mol triethylamine were dissolved in 200 ml of acetonitrile and placed in a reaction vessel. 0.25 mol diphenylphosphine chloride was dissolved in 60 ml of acetonitrile and added dropwise to the reaction vessel in portions. Nitrogen gas was continuously purged to replace the air during the process. After the addition was completed, the mixture was stirred continuously at 20 °C for 1.5 h. Then the temperature was raised to 85 °C and maintained for 18 h. The product was then separated, purified, and dried to obtain flame retardant 2 with a yield of approximately 81.3%.
[0043] Thermal performance test results: The melting temperature of this flame retardant is 213.8℃, and the initial decomposition temperature is 305.9℃.
[0044] FT-IR (KBr, cm -1 ): 3412 (NH), 2221 (-CN), 1518 (P-Ph), 1205 (P=O), 928 (PN).
[0045] Figure 5 The image shows the LC-MS spectrum of flame retardant 2. The results indicate that the molecular ion peak is located at m / z 256.9 [M+H]. + This is consistent with the expected molecular weight of the target flame retardant, which is 256.0 g / mol. Example 3
[0046] 0.25 mol iminodiacetonitrile and 0.25 mol triethylamine were dissolved in 200 ml of acetonitrile and placed in a reaction vessel. 0.25 mol diphenylphosphine chloride was dissolved in 60 ml of acetonitrile and added dropwise to the reaction vessel in portions. Nitrogen gas was continuously purged to replace the air during the process. After the addition was completed, the mixture was stirred continuously at 20 °C for 1.5 h. Then the temperature was raised to 85 °C and maintained for 18 h. The product was then separated, purified, and dried to obtain flame retardant 3 with a yield of approximately 79.6%.
[0047] Thermal performance test results: The melting temperature of this flame retardant is 224.1 ℃, and the initial decomposition temperature is 320.5 ℃.
[0048] FT-IR (KBr, cm -1 ): 2225 (-CN), 1499 (P-Ph), 1212 (P=O), 926 (PN).
[0049] Figure 6 The LC-MS molecular ion peak for flame retardant 3 is located at m / z 296.1 [M+H]. + This is consistent with the expected molecular weight of the target flame retardant, which is 295.2 g / mol. Example 4
[0050] 0.25 mol of 2-cyanoacetamide and 0.25 mol of triethylamine were dissolved in 200 ml of acetonitrile and placed in a reaction vessel. 0.25 mol of diphenylphosphine chloride was dissolved in 60 ml of acetonitrile and added dropwise to the reaction vessel. Nitrogen gas was continuously purged to replace the air during the process. After the addition was completed, the mixture was stirred continuously at 20 °C for 1.5 h. Then the temperature was raised to 85 °C and maintained for 18 h. The product was then separated, purified, and dried to obtain flame retardant 4, with a yield of approximately 82.6%.
[0051] Thermal performance test results: The melting temperature of this flame retardant is 216.7 ℃, and the initial decomposition temperature is 315.1 ℃.
[0052] FT-IR (KBr, cm -1 ): 3409 (NH), 2223 (-CN), 1650 (C=O), 1501 (P-Ph), 1214 (P=O), 925 (PN).
[0053] Figure 7 The image shows the LC-MS spectrum of flame retardant 4. The results indicate that the molecular ion peak is located at m / z 285.1 [M+H]. + This is consistent with the expected molecular weight of the target flame retardant, which is 284.1 g / mol. Example 5
[0054] 0.5 mol of p-aminobenzonitrile and 0.5 mol of triethylamine were dissolved in 200 ml of acetonitrile and placed in a reaction vessel. 0.25 mol of phenylphosphonic dichloride was dissolved in 60 ml of acetonitrile and added dropwise to the reaction vessel. Nitrogen gas was continuously purged to replace the air during the process. After the addition was completed, the mixture was stirred continuously at 20 °C for 1.5 h. Then the temperature was raised to 85 °C and maintained for 18 h. The product was then separated, purified, and dried to obtain flame retardant 5, with a yield of approximately 85.3%.
[0055] Thermal performance test results: The melting temperature of this flame retardant is 230.8 ℃, and the decomposition start temperature is 323.4 ℃.
[0056] FT-IR (KBr, cm -1 ): 3408 (NH), 2223 (-CN), 1503 (P-Ph), 1210 (P=O), 924 (PN).
[0057] Figure 8 The image shows the LC-MS spectrum of flame retardant 5. The results indicate that the molecular ion peak is located at m / z 359.2 [M+H]. + This is consistent with the expected molecular weight of the target flame retardant, which is 358.2 g / mol. Example 6
[0058] 0.6 mol aminoacetonitrile and 0.6 mol triethylamine were dissolved in 200 ml acetonitrile and placed in a reaction vessel. 0.25 mol phenylphosphonic dichloride was dissolved in 60 ml acetonitrile and added dropwise to the reaction vessel. Nitrogen gas was continuously purged to replace the air during the process. After the addition was completed, the mixture was stirred continuously at 20 °C for 1.5 h. Then the temperature was raised to 85 °C and maintained for 18 h. The product was then separated, purified, and dried to obtain flame retardant 6 with a yield of approximately 86.7%.
[0059] Thermal performance test results: The melting temperature of this flame retardant is 218.9 ℃, and the initial decomposition temperature is 309.4 ℃.
[0060] FT-IR (KBr, cm -1 ): 3411 (NH), 2223 (-CN), 1510 (P-Ph), 1215 (P=O), 926 (PN).
[0061] Figure 9 The image shows the LC-MS spectrum of flame retardant 6. The results indicate that the molecular ion peak is located at m / z 234.9 [M+H]. + This is consistent with the expected molecular weight of the target flame retardant, which is 234.1 g / mol. Comparative Example 1
[0062] 0.25 mol melamine and 0.25 mol triethylamine were dissolved in 200 ml acetonitrile and placed in a reaction vessel. 0.75 mol diphenylphosphine chloride was dissolved in 60 ml acetonitrile and added dropwise to the reaction vessel. Nitrogen gas was continuously purged to replace the air during the process. After the addition was completed, the mixture was stirred continuously at 20 °C for 1.5 h. Then the temperature was raised to 85 °C and the nucleophilic substitution reaction was carried out for 18 h. The product was then separated, purified, and dried to obtain flame retardant 7.
[0063] This embodiment uses a thermoplastic resin composition as an example of a flame-retardant polymer material to demonstrate its flame-retardant and anti-dripping effects.
[0064] Table 1 shows the composition formulations and properties of the thermoplastic resins in Examples 7-13 and Comparative Examples 2-8. The components of the compositions in Table 1 were weighed (by weight; 0.2 parts by weight of antioxidant 1098 and 0.2 parts by weight of antioxidant 168 were added to each example and comparative example composition, but are not shown in Table 1 again; those skilled in the art can choose whether to add antioxidants according to actual needs), mixed, melted, extruded, and granulated using a twin-screw extruder to prepare flame-retardant thermoplastic resins. The parameters such as the corresponding screw extruder temperature and speed, set according to the specific type of thermoplastic resin, are well known to those skilled in the art and will not be described further. Test specimens were injection molded according to the testing standard requirements.
[0065] The flame retardant properties of thermoplastic resins are characterized by flame retardant rating and limiting oxygen index, while the anti-dripping properties of thermoplastic resins are characterized by dripping amount.
[0066] Table 1 shows the components and properties of the thermoplastic resin compositions of Examples 7-13 and Comparative Examples 2-8.
[0067] As can be seen from Examples 7-13, the dripping amount of the thermoplastic resin composition with added Formula I flame retardant is less than 2 drops. Compared with Comparative Examples 2-8, this proves that the Formula I flame retardant of this application can effectively improve the anti-dripping performance of thermoplastic resin.
[0068] Meanwhile, the flame retardant of Formula I in this application can also effectively improve the flame retardant properties of thermoplastic resins, with a limiting oxygen index of over 26.7%, and a flame retardant rating of over V-1 at a thickness of 3.2 mm.
[0069] As seen in Examples 7-12, the dripping amount gradually decreased with the increase of the amount of Formula I flame retardant. After adding 15 parts of Formula I flame retardant, the thermoplastic resin composition could completely suppress the dripping. This may be because the Formula I flame retardant undergoes a triazine reaction under high combustion conditions, forming a network structure that restricts chain segment movement and increases the melt viscosity. As the amount of Formula I flame retardant increases, the melt viscosity gradually increases, making it difficult for the dripping droplets to fall, rather than through the mechanism of forming a dense carbon layer to prevent dripping. Figure 10 As can be seen, the thermogravimetric analysis and micro-thermogravimetric analysis of Example 7 under air showed that the thermoplastic resin composition of Example 7 completely decomposed at 700°C, with the final residue being almost 0%, which proves that the mechanism of this application is not carbonization to prevent dripping.
[0070] The flame retardancy rating of the thermoplastic resin composition in Example 11 dropped to V-1 at a thickness of 3.2 mm. This may be because the molten droplets stopped dripping, which prevented the resin from carrying away heat through the droplets during combustion, thus prolonging the combustion time. The gas phase effect was insufficient, and the flame could not be effectively extinguished. The flame retardancy rating of Example 12 rose to V-0. This may be because the amount of flame retardant in Formula I continued to increase, thereby improving the gas phase flame retardancy effect and extinguishing the flame quickly.
[0071] Depend on Figure 11 As can be seen, the addition of the flame retardant of Formula 1 to the thermoplastic composition in this application results in a significant increase in the melt viscosity of the composition only above approximately 340°C. This does not affect the melt processing of thermoplastic resins with processing temperatures below 340°C, especially extrusion and injection molding. Some cyano compounds with char-forming properties, although capable of improving flame retardancy and other properties through triazine crosslinking reactions, lead to a significant increase in melt viscosity during the melt processing of thermoplastic resin compositions. For example, a substantial increase occurs between 230 and 300°C, making direct application in the processing of thermoplastic resins almost impossible. For instance, the conventional melt processing temperature for PP is typically controlled between 190 and 260°C, while PET, PBT, PA6, and PA66 typically require extrusion and injection molding temperatures above 230°C. High-viscosity melts are difficult to melt process and can easily lead to incomplete injection molding, especially for thin-walled parts. This is likely due to the fact that the phosphono group is a strong electron-withdrawing group. This group can reduce the electron cloud density around the benzene ring and cyano group through the conjugation / induction effect with the amino group and benzene ring, thereby reducing the nucleophilic reactivity of the cyano group and increasing the activation energy of the crosslinking reaction. In addition, the amino group in the flame retardant molecule forms intermolecular and intramolecular hydrogen bonds with the phosphono group, which restricts molecular motion and makes it difficult for the cyano groups to approach and collide effectively, further delaying the crosslinking reaction. At the same time, the large size of the diphenylphosphono group forms a significant spatial shielding effect on the cyano group, hindering the crosslinking of the cyano group. In summary, this flame retardant can control the crosslinking reaction to occur only during combustion, rather than during resin processing, which would lead to processing and molding difficulties.
[0072] It should be noted that the flame retardant of Formula 1 increases the melt viscosity mainly due to the formation of a triazine structure by cyano crosslinking. The intrinsic activation energy of its crosslinking reaction is less affected by the resin matrix. In different thermoplastic resins (such as polyamide, polyester, polypropylene, etc.), the starting temperature of 340℃, which significantly increases the melt viscosity, has little effect.
[0073] As can be seen from Example 13, the thermoplastic resin composition containing the flame retardant of Formula I exhibits excellent anti-dripping effect after the addition of talc, and the flame retardant rating can still reach V-0.
[0074] As can be seen from the comparison of Example 7 and Comparative Examples 2 and 3, although adding 12 parts of flame retardant 7 or melamine with a triazine structure directly to the thermoplastic resin composition slightly improves the anti-dripping performance, the overall flame retardant rating at a thickness of 3.2 mm is only V-2. This may be because the amount is insufficient to effectively improve the flame retardant and anti-dripping performance through mechanisms such as char formation. In contrast, the flame retardant of this application can achieve a flame retardant rating of V-0 at a thickness of 3.2 mm with an addition amount of 10 parts. It can be seen that the mechanism of action of this application is different from that of directly adding triazine compounds, and the anti-dripping performance is also significantly different.
[0075] It should be noted that the embodiments in this application are merely examples of specific implementation methods and are not intended to limit the scope of protection of this application. Those skilled in the art can replace the same or similar components according to actual needs, and all such replacements are within the scope of protection of this application.
Claims
1. A flame retardant with anti-dripping function, characterized in that, Including flame retardants with Formula I structure: Formula I, R1 is selected from phenyl or phenoxy. R2 is selected from hydrogen and cyano. R3 is selected from one of methylene, ethylene, phenyl, and acetylated groups. The R4 is either R1 or N-R2(R3-CN), and the N-R2(R3-CN) group is connected to the P in Formula I through N.
2. The flame retardant according to claim 1, characterized in that, The flame retardant is selected from one or more of the structural flame retardants (1) to (7). 。 3. The flame retardant according to claim 1, characterized in that, It is prepared by a nucleophilic substitution reaction of a phosphoryl chloride compound and an aminocyanide, wherein the phosphoryl chloride compound includes one or more of diphenyl chlorophosphate, phenylphosphonic dichloride, and diphenylphosphine chloride.
4. The flame retardant according to claim 3, characterized in that, The aminocyanide includes one or more of aminoacetonitrile, 3-aminopropionitrile, iminodiacetonitrile, m-aminobenzonitrile, 2-aminobenzonitrile, cyanoacetamide, and p-aminobenzonitrile.
5. The method for preparing the flame retardant according to any one of claims 1 to 4, characterized in that, Includes the following steps: Flame retardants of Formula I are prepared by nucleophilic substitution reaction of phosphoryl chloride compounds with aminocyanides and by one or more post-treatment methods such as separation, purification, and drying as needed.
6. The preparation method according to claim 5, characterized in that, The molar ratio of the phosphoryl chloride compound to the aminocyanide is 1:(1~2.5).
7. The preparation method according to claim 5, characterized in that, The nucleophilic substitution reaction was carried out at a temperature of 70-90 °C for 16-20 h.
8. A thermoplastic resin composition, characterized in that, Including the flame retardant with anti-dripping function as described in any one of claims 1 to 4.
9. The thermoplastic resin composition according to claim 8, characterized in that, The thermoplastic resin composition uses one or more of polyamide, polyester, and polyolefin resins as the resin matrix, and the flame retardant of Formula I is a non-reactive flame retardant.
10. The thermoplastic resin composition according to claim 8, characterized in that, It also includes one or more of the following: reinforcing fillers, thermally conductive fillers, antioxidants, lubricants, toughening agents, antistatic agents, laser marking agents, and color powders.
11. The thermoplastic resin composition according to claim 8, characterized in that, By weight, it includes the following components: 62-92 parts of thermoplastic resin; Flame retardant 8-25 parts; 0-20 parts of mineral powder; The sum of the above components is 100 parts by mass.
12. The thermoplastic resin composition according to claim 8, characterized in that, By weight, it includes the following components: 86-90 parts of thermoplastic resin; 10-14 parts flame retardant; The sum of the above components is 100 parts by weight, and the composition achieves a flame retardant rating of V-0 at a thickness of 3.2 mm.